STUDENTS' LEGAL AWARENESS OF DRIVING LICENSE OWNERSHIP AT MOYUDAN MUHAMMADIYAH 1 VOCATIONAL SCHOOL - Putri, Indah Lestari; Wahyuningsih, Tri (Jurnal Meta-Yuridis, 2024)
The research aims to determine students' legal awareness of owning a driving license at SMK Muhammadiyah 1 Moyudan. This research uses qualitative research with an empirical juridical approach. The research subjects were grade 10 students who drove motorbikes without driving licenses and vice principals, while the objects were students' legal awareness of owning a driving license. Methods of data collection using interviews and documentation then checking the truth of the source using triangulation of sources and techniques. The results of the study show that students who know the conditions for driving a motorcycle must have a driving license. They do not understand in detail the contents, benefits, and objectives of Article 77 Paragraph (1). All students accept and positively support the existence of these regulations. The legal awareness of students in complying with this article is classified as negative legal awareness because they do not yet have a driver's license, so they are influenced by other factors, namely parents, lack of public transportation, and the school does not prohibit students from bringing motorcycles to school.